Methodical approaches to the economic assessment of costs in the operation of cars with axial load of 27 tons at the section Kachkanar—Smychka - G. A. Granovskaya; A. I. Safonova; O. A. Suslov; N. S. Okhotnikov (Вестник Научно-исследовательского института железнодорожного транспорта, 2018)
Abstract. The most important direction of increasing the efficiency of rail transportation is to increase the load-carrying capacity of freight cars as a result of an increase in axial loads. New car 12-9548-01 with improved technical characteristics has an axial load of 27 tons. The article describes method of calculating the coefficient reflecting the change in the impact of cars with an axial load of 27 tons on the roadbed during transportation in estimated cars compared to transportation in equivalent cars. Algorithms for calculating changes in the cost of fuel and energy costs for train traction and maintenance of the track infrastructure on the site during the operation of trains formed from cars with an axial load of 27 tons are given, as well as methods for determining the initial data for the calculation.Authors provide values of the coefficient reflecting the change in the impact of vertical and horizontal forces on the railway line when passing freight cars with an axial load of 27 tons compared to analogue cars, and the coefficient of change of the main specific resistance to motion separately for loaded and empty cars.Developed calculation algorithms and methods for obtaining baseline data allow an economic assessment of changes in infrastructure maintenance costs and fuel and energy resources for the operation of trains formed from cars with an axial load of 27 tons compared to those formed from cars with a load of 23.5 tons at the experimental section Kachkanar—Smychka.The cost change assessment carried out in 2017 shows a generally definite economic effect, while there is a reduction in costs associated with the consumption of electricity for train traction as a result of the operation of the estimated cars in the experimental section and an increase in the cost of maintaining the track superstructure and the roadbed, which is quite expected for the conditions of the organization of traffic with increased axial loads.